Pengaruh Komposisi Media Tanam Organik Terhadap Hasil Tanaman Sawi (Brassica juncea L.): The Effect of Organic Planting Media Composition on the Yield of Mustard Plants (Brassica juncea L. ) - Herawati, Jajuk; Indarwati, Indarwati; Christiantoro, Bernandi Aprila (Journal of Applied Plant Technology, 2023)
The purpose of the study was for various compositions of growing media on the yield of mustard plants (Brassica juncea L.). The method used in this study was a complete randomized design (CRD) with 6 treatments and each treatment was repeated 5 times. The treatment made is K0: Soil Media only; K1: Soil Media + Compost (2 : 1); K2 : Soil Media + Compost + Goat Manure (2 : 1 : 1); K3: Soil Media + Compost + Cocopeat (2 : 1 : 1); K4: Soil Media + Compost + Cow Manure (2 : 1 : 1); K5: Soil Media + Compost + Chicken manure (2 : 1 : 1). The results showed that the treatment of the composition of the planting media tried had the same effect on all observation parameters: plant length, number of leaves, and wet weight of mustard plants. With various media composition treatments tried, mustard plants are able to produce wet weight of mustard plants weighing 25.32 g – 118.5 g / polybag.